2012
DOI: 10.1021/bc300128r
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation and Biodistribution of an anti-MUC1 Aptamer in MCF-7 Tumor-Bearing Mice

Abstract: Aptamers are characterized by a rapid renal clearance leading to a short in vivo circulating half-life. In order to use aptamers as anticancer therapeutic agents, their exposure time to the tumor has to be enhanced via increasing residency in the bloodstream. A way to achieve this goal is by conjugating the aptamer to poly(ethylene glycol) (PEG). Herein, we present the conjugation of a bifunctionalized anti-MUC1 aptamer (NH(2)-AptA-SR) with the (99m)Tc coordinating moiety MAG2 and either a conventional branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 18 publications
1
60
1
Order By: Relevance
“…An increasing accumulation of radiolabelled aptamer in time (up to 5 h p.i.) has been often observed with other aptamers [19,20,[47][48][49].…”
Section: Tumour Uptakementioning
confidence: 77%
“…An increasing accumulation of radiolabelled aptamer in time (up to 5 h p.i.) has been often observed with other aptamers [19,20,[47][48][49].…”
Section: Tumour Uptakementioning
confidence: 77%
“…[21][22][23] These aptamers have been selected against the APDTRPAPG synthetic peptide of the MUC1 tandem repeat sequence using traditional SELEX approaches. The structure of this anti-MUC1 aptamer has also been studied by nuclear magnetic resonance 33 and deposited in Protein Data Bank.…”
Section: Methodology Aptamersmentioning
confidence: 99%
“…21 In addition, they have been capable of detecting circulating MUC1 in sandwich enzyme-linked immunosorbent assays, improving current detection limits, 19 and have been extensively studied as radiopharmaceuticals for their potential in gamma-camera and single-photon emission computed tomography (SPECT) imaging. [21][22][23] Furthermore, they have been shown to be particularly promising agents in photodynamic therapy as phototoxic agents 24 and delivery agents of standard chemotherapy such as doxorubicin. 25 Finally, the MUC1 aptamers have been successfully used in nanoparticle (NP) formulation, described both from our own group 26 for silica NPs and from a different group for liposomal formulation in conjunction with paclitaxel.…”
mentioning
confidence: 99%
“…This is a remarkable result which revealed that the accumulation of S1-apMUC1-Tc nanoparticles in tumours was significantly larger compared with the bioaccumulation of the free MUC1 aptamer labelled with 99m Tc (vide infra). [49][50][51] Marked accumulation was also observed in the upper part of the image, which correlated with the injection site (retro-orbital). Figure 5B depicts the bioluminescence imaging that indicates the tumour position which correlated with planar images; accumulation of the S1-apMUC1-Tc nanoparticles by the tumour, as observed by comparing bioluminescence (red and yellow spots in Figure 5B) and planar images.…”
Section: Resultsmentioning
confidence: 76%
“…Mesoporous supports can be prepared in different forms that range from micrometric to nanometric, and have tailor-made pores (2-10 nm in diameter) and a very large specific surface areas (up to 1200 m 2 g -1 ). 49 Given these remarkable features, mesoporous materials have a huge loading capacity and can store not only small but also a wide variety of medium-sized molecules such as proteins, oligonucleotides and nucleic acids. These supports are also 48 chemically inert under a wide range conditions and are easily functionalized using well-known chemistries.…”
Section: Synthesis Of Mesoporous Silica Materialsmentioning
confidence: 99%